Internet bad information detection based on Bert model - Xin CAI (Dianxin kexue)
In view of the business scenario of bad information detection on the internet,the method of detection based on the text content of the website was discussed .Classical text analysis techniques were reviewed.The key technical features and two different usages of Bert model were introduced.The specific implementation scheme of using the feature extraction method to detect website bad information was described in detail,and was compared with the traditional TF-IDF model and word2vec+LSTM model.The validity of this method is verified.